Comparative Variations of Words in Translation on the Example of English and Uzbek - Sotvoldiyevna, Dona; Zаfаrjon, Djаlolov (PT. Antis International Publisher, 2024)
Nowadays, special attention is paid to foreign languages in our country, especially the study of English. Every year, several decrees and resolutions on the development of foreign languages are adopted by the head of state and our government. This means how important it is to learn foreign languages. In this article, a comparative change of words in translation will be considered on the example of English and Uzbek, and opinions and considerations will be made.